Of pipes, persons, and patients. Issue 2 (1st December 2002) - Sayers, G M
Abstract : Michel Foucault's analysis of Magritte's painting, Ceci N'est Pas Une Pipe, and the later work, Les Deux Mystéres, serves as a template, that is broadened to consider different representations of persons and patients. Kant's noumenal person is contrasted with phenomenal persons, and the well individual is contrasted with the patient. Patients may be considered as the subject or object of illness, and both versions are "imprisoned" within a psychological and social context that curtails freedom, threatens continuity of existence, and may question the nature of their personhood.